Sanitizing efficacy and antimicrobial mechanism of peracetic acid against histamine-producing bacterium, Morganella psychrotolerans. (May 2020) - Wang, Di; Yamaki, Shogo; Kawai, Yuji; Yamazaki, Koji
Abstract: In this study, we aimed to investigate the sanitizing effects of peracetic acid (PAA), and the underlying mechanism of its antimicrobial action against Morganella psychrotolerans . The exposure of M. psychrotolerans to 20 ppm PAA for 5 min led to its decrease below the detection level, indicating that PAA has a significant antibacterial effect against M. psychrotolerans in vitro . Moreover, the viable counts of M. psychrotolerans on saury ( Cololabis saira ) surface were showed a reduction of 1.40 and 2.23 log CFU/cm 2 upon treatment with 80 ppm PAA for 1 and 5 min, respectively. Further, PAA treatment delayed the growth of M. psychrotolerans on saury surface during storage at 4 °C. Next, the antimicrobial mechanism of PAA against M. psychrotolerans cells was investigated, and the damage to the cell membrane and cell surface upon PAA treatment was observed using scanning electron microscopy (SEM) and epifluorescence microscopy. The chromosomal DNA and the protein profiles after PAA treatment were also analyzed. Form our results, we hypothesized that the bactericidal effect of PAA treatment was mainly attributed to damage the bacterial cell membrane. These results indicate that PAA may be an efficient disinfectant against M. psychrotolerans and has applications in seafood processing and storage. Highlights: PAA had good sanitizing efficacy for against M. psychrotolerans in vitro. Washing with PAA was able to reduce M. psychrotolerans populations on saury surfaces. PAA caused bacterial death by disrupting the cell membrane.